Housing preference of residents in Ile-Ife, Nigeria - Adewale Olufunlola Yoade (Economic and Environmental Studies (E&ES), 2016)
Choosing where to live is a profound decision that affects residents' income, social interactions, health and safety, as well as daily activities. The study investigates housing preference of residents within the city of Ile- Ife, Nigeria. Data for the study were obtained from both primary and secondary sources. Data obtained include quality of the environment in terms of good layout, availability of infrastructural facilities like good roads, water supply, quietness, peace and adequate security etc.; socio-cultural activities; accessibility to place of work; vacant plot; security of land ownership; and closeness to the place of birth. 309 households were surveyed using multistage sampling. The finding reveals that majority (84.4%) of respondents' in Iremo have no education at all while most (88.5%) of the respondents' in Parakin have tertiary education. In Igboya, 54.5% of the respondents has tertiary education. Also, among the most important determinants of residential district preferences within the study area are factors that deal with the quality of the environment (31.0%) and those that are socio-cultural in nature (42.0% ). The study established that great differences appear in the determinants of households' preferences for different residential density districts. The study concluded that each category of residential density district of a city has distinct set of determinants of households' residential district preferences peculiar to it.
Keywords: D10; D31; D32; 330; housing; preference; choice; residents' and Ile-Ife